Prevalence of heroin and methamphetamine male users in the northern Taiwan, 1999-2002: capture-recapture estimates - Sun Hsiao-Ju; Chang Yuan-Ying; Chen Chuan-Yu; Chiang Shu-Chuan; Chen Wei J (BMC, 2007)
Abstract Background Illegal drug use and related problems have been emerging as an important public health issue in Taiwan. Via the capture-recapture approach, the present study aimed to offer insights into the size of heroin and methamphetamine male user population in the northern Taiwan during the period from 1999 to 2002. Methods Annual lists of male subjects were collated from both judiciary and medical systems in Taoyuan County, Taiwan. A total of 2809, 2486, 1661, and 1440 local male illegal drug users aged 15 to 54 years were identified in Taoyuan County from 1999 to 2002, respectively. Results An estimated number of 16192, 14532, 16844, and 11783 local male methamphetamine or heroin users were found in each of the four consecutive years in the region. From 1999 to 2002, the annual prevalence rate for heroin use was 0.27% (95% CI = 0.20%, 0.38%), 0.33% (95% CI = 0.25%, 0.44%), 0.63% (95% CI = 0.44%, 0.92%), and 0.72% (95% CI = 0.54%, 0.97%), respectively, suggesting a trend of significant increase (chi-square for linear trend = 1677.76, d.f. = 3, p < 0.0001). In contrast, a decreasing trend was found for methamphetamine (2.38%, 1.91%, 2.47%, and 1.24%), with a modest rebound in 2001. The prevalence rates of illegal drug use for male residents in Taoyuan County were approximately 2-3% during this period, and the scale of problem shows no sign of diminution. Conclusion By taking advantage of existing datasets that were incomplete by each alone, the approach of capture-recapture model may be ultimately considered as a tool to estimate the scale of illegal drug use problems. The population of heroin-using males apparently is stably expanding in the northern part of Taiwan in the first years of 21st century.